2009
DOI: 10.5194/acp-9-8573-2009
|View full text |Cite
|
Sign up to set email alerts
|

Source apportionment of fine organic aerosols in Beijing

Abstract: Abstract. Fine particles (PM 2.5 , i.e., particles with an aerodynamic diameter of ≤2.5 µm) were collected from the air in August 2005, August-September 2006, and JanuaryFebruary 2007, in Beijing, China. The chemical compositions of particulate organic matter in the ambient samples were quantified by gas chromatography/mass spectrometry. The dominant compounds identified in summertime were n-alkanoic acids, followed by dicarboxylic acids and sugars, while sugars became the most abundant species in winter, foll… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
65
4
2

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(82 citation statements)
references
References 37 publications
9
65
4
2
Order By: Relevance
“…Some studies have given the general characteristics of PM 2.5 chemical compositions and discussed their seasonal variations, correlations, or sources (He et al, 2001;Sun et al, 2004;Song et al, 2006). Some studies have focused on the concentrations, correlations, sources or formation of some specific species (such as inorganic ions, carbonaceous components, or organic matters) of PM 2.5 in Beijing (Yao et al, 2002;Dan et al, 2004;Huang et al, 2006;Wang et al, 2009;Pathak et al, 2009;Ianniello et al, 2011). In addition, the size distributions of aerosol chemical species Cheng et al, 2009;Guo et al, 2010;Li et al, 2012), aerosol number concentrations or new particle formation processes Yue et al 2009Yue et al , 2011Shen et al, 2011;Zhang et al, 2011;Gao et al, 2012), and aerosol optical characteristics or mixing state (Cheng et al, 2009;Deng et al, 2011;Ma et al, 2011Ma et al, , 2012Chen et al, 2012) have also been discussed for Beijing and the surrounding region.…”
Section: P S Zhao Et Al: Concentrations and Chemical Compositions mentioning
confidence: 99%
“…Some studies have given the general characteristics of PM 2.5 chemical compositions and discussed their seasonal variations, correlations, or sources (He et al, 2001;Sun et al, 2004;Song et al, 2006). Some studies have focused on the concentrations, correlations, sources or formation of some specific species (such as inorganic ions, carbonaceous components, or organic matters) of PM 2.5 in Beijing (Yao et al, 2002;Dan et al, 2004;Huang et al, 2006;Wang et al, 2009;Pathak et al, 2009;Ianniello et al, 2011). In addition, the size distributions of aerosol chemical species Cheng et al, 2009;Guo et al, 2010;Li et al, 2012), aerosol number concentrations or new particle formation processes Yue et al 2009Yue et al , 2011Shen et al, 2011;Zhang et al, 2011;Gao et al, 2012), and aerosol optical characteristics or mixing state (Cheng et al, 2009;Deng et al, 2011;Ma et al, 2011Ma et al, , 2012Chen et al, 2012) have also been discussed for Beijing and the surrounding region.…”
Section: P S Zhao Et Al: Concentrations and Chemical Compositions mentioning
confidence: 99%
“…In previous studies, it was reported that COA accounted for 14-25 % (∼ 20 % on average) of the total OA in summer and winter in Beijing, with an average concentration (∼ 6 µg m −3 ), which is a relatively stable component of OA (Hu et al, 2016a;Wang et al, 2009). In this study, the concentrations and proportions of COA in OA during seasonal observations were in the range of 2.5-5.2 µg m −3 and 15-28 %, respectively, comparable to previous results.…”
Section: Investigating Oa Sources With Pmfmentioning
confidence: 99%
“…In contrast, the coarse mode radius in the pollution period was about 0.06-0.38 µm less than that in the non-pollution period. It could be speculated that the higher wind speed during non-pollution periods results in more coarse particles in the atmosphere such as, for instance, the fugitive dust (Wang et al, 2009) and fly ash emissions from coal burning (Yang et al, 2009). …”
Section: Inter-comparison Of Aerosol Optical Properties During Pollutmentioning
confidence: 99%